Development of an Augmented Reality environment for the assembly of precast wood-frame wall from the BIM model - Cuperschmid, Ana Regina Mizrahy (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2016)
This article presents the development of an Augmented Reality (AR) application to assist the assembly of a precast wood-frame wall from the BIM model of the wall execution sequence. The research was outlined according to the Design Science Research approach and aims the development of an AR application named “montAR” (version 2.0). This application offers a tutorial that combines a wall model visualized in AR in actual scale, followed by an audio with step-by-step instructions of the assembly process. Its applicability was simulated in a laboratory with the participation of volunteers (architecture and engineering students). Two visualization gadgets were used and compared: smartphone and smart glasses. The potentialities and difficulties of the use of the AR system were verified through a questionnaire answered by the participants and through direct observation and result analysis by the researchers. The results demonstrated the potential of the use of AR for precast wall assembly. From a technological innovation perspective, this study emphasizes the potential use of AR as a technology suitable for training and for construction quality control.